Antivirals against HCV infection: the story thus far - Ahmad Adebayo Irekeola; Engku Nur Syafirah EAR; Nur Amalin Zahirah Mohd Amin; Nazri Mustaffa; Rafidah Hanim Shueb (Journal of Infection in Developing Countries)
Remarkable scientific breakthroughs have been made in the stride towards the development of potent and tolerable hepatitis C regimens within the last three decades. Earlier approaches involved the use of pegylated interferon alfa and ribavirin as standard-of-care treatment. Treating genotype 1a infection with this regimen which was at that time considered the gold standard for hepatitis C virus therapy was rife with challenges; safety and toxicity issues necessitated a rigorous quest for alternative regimens. Deeper understanding of the pathogenesis of hepatitis C virus ushered in the era of direct acting antiviral agents. These agents have been the subject of intensive research in the last two decades, leading to the development of drug classes such as protease inhibitors (e.g., grazoprevir), NS5A inhibitors (e.g., daclatasvir) and NS5B inhibitors (e.g., sofosbuvir). While many are still under development, several have been approved for hepatitis C therapy. A number of studies investigating the combination of direct acting antiviral agents with or without pegylated interferon and/or ribavirin for the treatment of chronic hepatitis have demonstrated sustained virologic response of > 90%. Given the array of direct acting antiviral agents currently available, the present landscape of hepatitis C therapy is now characterized by a gradual transition to all-oral interferon-free regimens. Despite these milestones, the WHO global target of eliminating hepatitis C as a public health problem by 2030 seems uncertain. In this review, we provide a concise account of the evolution and advancements in the development of anti-HCV regimens.